Implementing Digital Governance for Improved Public Service Delivery - Amarachi Nwosu (Asian Digital Governance Problems, 2024)
Purpose: This study examines the implementation of digital governance and its impact on public service delivery in Lagos during 2024, focusing on accessibility, efficiency, transparency, and citizen satisfaction. Subjects and Methods: The research employed a mixed-methods approach using a convergent parallel design. Quantitative data were collected through questionnaires distributed to 250 residents who had experience using digital public services, while qualitative data were obtained from semi-structured interviews and focus group discussions involving policymakers, ICT administrators, public service officers, and citizens. Quantitative data were analyzed using SPSS through descriptive and inferential statistics, while qualitative findings were examined using thematic analysis. Results: The findings indicate that digital governance improved administrative efficiency, service accessibility, and procedural transparency. However, infrastructural instability, internet affordability, limited digital literacy, and institutional resistance continued to hinder implementation effectiveness. Efficiency emerged as the strongest factor influencing citizen satisfaction. Conclusions: Sustainable digital governance requires inclusive infrastructure development, institutional adaptation, and continuous digital literacy improvement.